The Word Study That Sticks Companion : Classroom-Ready Tools for Teachers and Students, Grades K-6. - Koutrakos, Pamela A. (Corwin literacy., 2019)
Kickstart joyful independent word study practice in your K-6 classroom Pamela Koutrakos offers a plethora of tools and ready-to-go resources to help teachers put the inquiry-based structures, lessons, and routines she delivered in her first book, Word Study That Sticks, into action. Loaded with teacher-facing resources such as planning and assessment tools, and student-facing tools such as reproducible minicharts, choice checklists, and self-assessments, The Word Study That Sticks Companion includes routines and materials that can be used within any word study curriculum. Let students take cha.